Growth and yield of cherry tomato (Solanum lycopersicum) as influenced by different types of staking and inorganic fertilizers - Md. Julfikar Ali Khan; Md. Harun Ar Rashid (Fundamental and Applied Agriculture, 2021)
Cherry tomato is an attractive, delicious, nutritious and healthy fruit, which is very appealing to consumers. The demand of cherry tomato in the market is increasing day by day because of its superior quality and better sweet taste compared to large table tomatoes. A field experiment was conducted at the Landscaping Section of the Department of horticulture, Bangladesh Agricultural University, Mymensingh during the period from October 2018 to April 2019 to study the growth and yield of cherry tomato as influenced by determine the effects of different types of staking and inorganic fertilizers on the. The experiment included three types of staking viz., S0 = Single staking, S1 = Double staking, S2 = Trellis and five different levels of inorganic fertilizers treatment viz., T0 = Control, T1 = Nitrogen (N) @ 181 kg/ha, T2 = Phosphorus (P) @ 160 kg/ha, T3 = Potassium (K) @ 142 kg/ha, T4 = N+P+K @ (181+160+142) kg/ha. The experiment was laid out in the randomized complete block design with three replications. Different types of staking and inorganic fertilizers had significant influence on all the growth and yield contributing parameters under study. Results revealed that all the growth and yield parameters showed better performance in trellis plants along with N+P+K @ (181+160+142) kg/ha like highest plant height (150.84 cm), number of leaves (38.71) and branches per plant (7.56), longest leaf length (36.14 cm), maximum number of flower clusters (26.48), flowers (786.99) and fruits per plant (310.67), longest fruit length (4.4 cm) and diameter (2.9 cm), maximum individual fruit weight (10.0 g) and highest fruit yield (93.0 t/ha) while the parameters gave the lowest value from single staked plants with control. Therefore, trellis along with combined application of N+P+K @ (181+160+142) kg/ha was found to be better in respect of growth and yield of cherry tomato. [Fundam Appl Agric 2021; 6(3.000): 245-256]